Exploring Accounting Teachers’ Effective Implementation of Assessment for Learning in the Classroom - Motsoeneng, Thabiso Jonah; Moreeng, Boitumelo (Research in Social Sciences and Technology- OpenED Network, 2023)
In this empirical paper, we discuss the factors impacting Accounting teachers’ effective implementation of assessment for learning (AfL) in the classroom and the action on the possible solutions in dealing with the impeding factors. AfL is considered a critical requirement for Accounting teachers and, if implemented effectively, improves the quality of learning. However, factors such as deficient subject and pedagogical content knowledge, inadequate assessment literacy and a lack of effective feedback have a significant impact on the effective implementation of AfL. Critical pedagogy framed the study theoretically and interrogated the factors impacting Accounting teachers in implementing AfL in the classroom and created an environment wherein teachers may share best practices relating to the administration of tasks. The qualitative research approach was utilised as a methodology, and Participatory Action Research was used as a research design. Thematic analysis was used to classify, analyse and interpret the data to get in-depth knowledge from the participants, who had to be in possession of a professional teaching qualification in Accounting and actively taught the subject in school for the past five years. The study findings indicate a need to develop and support teachers in implementing AfL to provide opportunities to identify learning gaps and devise scaffolding strategies to assist learners. Accounting teachers were equipped with the knowledge and skills to construct quality AfL tasks to assist the learners in acquiring the necessary expertise, skills and values in the subject.